2021
DOI: 10.25105/ber.v21i1.9231
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Authentic Leadership and Strategic Management Skills on Organization Performance Mediated by Knowledge Management at TNI Academy

Abstract: <p><em>This study aims to analyze the influence of Authentic Leadership and Strategic Management Skills on Organizational Performance mediated by Knowledge Management at the Indonesia Armed Force (TNI) Academy. This study tested seven hypotheses with structural equation modeling using the LISREL Ver.8.7 application. The sample of this research is 304 personnel of the TNI Academy.</em></p><p><em>The results of this study found six hypotheses were accepted and one hypothesis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
4

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 18 publications
2
1
4
Order By: Relevance
“…This finding is in line with empirical studies conducted by Umar, et al, (2021), D'Intino, et al, (2022, Mazzetti, et al, (2022). Ansong.…”
Section: Hypothesissupporting
confidence: 92%
See 3 more Smart Citations
“…This finding is in line with empirical studies conducted by Umar, et al, (2021), D'Intino, et al, (2022, Mazzetti, et al, (2022). Ansong.…”
Section: Hypothesissupporting
confidence: 92%
“…Hypothesis 1 obtained an estimated coefficient value of 0.303 which means that the increase in Strategic Leadership will increase performance in realizing Naval Officers who are ready to fight (Ready to Forces) and vice versa. The p-value of the t statistic is 0.001 <0.05, so Ho is rejected and it can be concluded that it is proven to have a positive effect on performance in realizing Navy officers who are ready to fight (Ready to Forces) Strategic Leadership.These findings support empirical studies conducted by Nakir, et all, 2020, Umar, et al, 2021, Suprianto, et al, 2021, Rizaldi, 2019, Rianto, et al, 2021, Sumaryadi, at all. 2021, it can be concluded that strategic leadership has a significant effect on performance and this finding is the same as the results of research at the Naval Academy conducted on lecturers, officers and the Academic Community of the Naval Academy.…”
Section: Decryption Of Research Objectssupporting
confidence: 89%
See 2 more Smart Citations
“…This indicates that: leadership in marine transportation and logistics companies has not utilized the Knowledge Management process as part of a strategy to empower ship crews to achieve organizational goals. The results of this study differ from the findings ofBaloch et al (2022): effective leadership and Organizational Culture influence the achievement of good Organizational Performance;Pramandita et al (2021): authentic leadership and strategic management skills have a positive and significant impact on Organizational Performance, apart from that, Knowledge Management directly or indirectly has a positive and significant impact on Organizational Performance;Ting et al (2021):…”
contrasting
confidence: 92%